Where's the Teacher? How Teacher Workplace Segregation Impedes Teacher Allocation in India - Sonja Fagernäs; Panu Pelkonen (Institute of Labor Economics (IZA), 2017)
Social or ethnic segregation can impede the equitable allocation of public resources in developing countries. We study an under-explored dimension; the allocation of public sector teachers in India. Using a register database for 2006-12, we construct indicators for the equality of teacher allocation and workplace segregation of teachers by gender and caste within districts. While pupil-teacher ratios have improved, the equality of teacher allocation has not. We show that allocation and segregation are connected; in districts with a higher degree of initial teacher segregation, a lower share of schools met pupil-teacher norms imposed by the Right to Education Act (2009).
Keywords: H75; I24; J45; M54; 330; teachers; public service delivery; segregation; caste; India; right to education